Economic policy for digital attention intermediaries - Martin Peitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This report provides an overview on the economics of attention intermediaries. It addresses the following questions: What are the economics of attention intermediaries? For competition policy, how should markets be defined and market power of attention intermediaries be assessed? What theories of harm in merger control and abuse of dominance possibly apply to attention intermediaries? The report also touches on consumer protection policies and other regulatory issues.
Keywords: 330; attention intermediaries; platforms; market power; regulation; digital markets